2022
DOI: 10.3390/foods11111609
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pesticide Residue Level in Grape Using Hyperspectral Imaging with Machine Learning

Abstract: Rapid and accurate detection of pesticide residue levels can help to prevent the harm of pesticide residue. This study used visible/near-infrared (Vis-NIR) (376–1044 nm) and near-infrared (NIR) (915–1699 nm) hyperspectral imaging systems (HISs) to detect the level of pesticide residues. Three different varieties of grapes were sprayed with four levels of pesticides. Logistic regression (LR), support vector machine (SVM), random forest (RF), convolutional neural network (CNN), and residual neural network (ResNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…This was attributed to the moisture change in the Hami melon. The pesticide residues did not change the position of the spectral feature absorbance peaks, and it agreed with previous studies such as Ye et al [ 21 ], Yu et al [ 23 ], and Sun et al [ 36 ]. The spectral curves of different pesticide residue contents in different mature periods overlapped partially, and the difference was not obvious.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This was attributed to the moisture change in the Hami melon. The pesticide residues did not change the position of the spectral feature absorbance peaks, and it agreed with previous studies such as Ye et al [ 21 ], Yu et al [ 23 ], and Sun et al [ 36 ]. The spectral curves of different pesticide residue contents in different mature periods overlapped partially, and the difference was not obvious.…”
Section: Resultssupporting
confidence: 92%
“…This result was obviously better than other models. However, it was lower in comparison to Ren et al [ 41 ], who used the chisquare test combined with linear discriminant analysis, and Ye et al [ 21 ], who used ResNet or logistic regression. However, they did not measure the actual residue contents, and divided residue levels according to the ratio of pesticides to water.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In the study of identifying cocoa beans, a comparison of a deep computer vision system with a conventional computer vision system revealed that the former was more accurate [ 70 ]. Studies to detect pesticide residue levels have shown that deep learning outperforms traditional machine learning [ 71 ]. In a study of barley flour classification, machine learning methods were used to show superior predictive power compared to computer vision systems [ 72 ].…”
Section: Discussionmentioning
confidence: 99%